2021
DOI: 10.1111/ppl.13472
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides from microalgae: Focus on anti‐cancer and immunomodulating activity

Abstract: In addition to the rapidly expanding field of using microalgae for food and feed, microalgae represent a tremendous potential for new bioactive compounds with health-promoting effects. One field where new therapeutics is needed is cancer therapy. As cancer therapy often cause severe side effects and loose effect due to development of drug resistance, new therapeutic agents are needed. Treating cancer by modulating the immune response using peptides has led to unprecedented responses in patients. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 87 publications
(100 reference statements)
1
23
0
Order By: Relevance
“…In this context, anticancer peptides have emerged as a new approach in the treatment of cancer. In the last two decades, natural peptides with anticancer properties have been isolated from several organisms, including mammals 39 , fish 40 , sponges 41 , molluscs 42 , amphibians 43 and algae 44 . The present study, in turn, gathered evidence on the anticancer effect of the peptide melittin, from the venom of Apis spp.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, anticancer peptides have emerged as a new approach in the treatment of cancer. In the last two decades, natural peptides with anticancer properties have been isolated from several organisms, including mammals 39 , fish 40 , sponges 41 , molluscs 42 , amphibians 43 and algae 44 . The present study, in turn, gathered evidence on the anticancer effect of the peptide melittin, from the venom of Apis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae peptides that mimic the functions of mediators involved in pathologic processes responsible for vascular damage playing a putative role in the prevention of cardiovascular disease were discussed by Li et al [ 212 ]. Cancer-inhibiting or immunomodulating effects of microalgae have been reported, although the number of reports on bioactive peptide sequences is very limited [ 259 ]. These studies, antioxidant and ACE potential have been confirmed in vitro for other microalgae hydrolysates obtained from C. vulgaris , Porphyra dioica , Fucus spiralis [ 234 , 260 , 261 ].…”
Section: Bioactive Properties Of Non-meat Proteinsmentioning
confidence: 99%
“…Various groups of algae such as Arthrospira platensis (spirulina) and Chlorella are excellent sources of protein (up to 70% dry wt.) (Wells et al, 2017) and, therefore, were explored for their peptides with bioactive properties such as anticancer and immunomodulating activity (Skjånes et al, 2021). Similarly, hydrolysis of marine microalgae with a range of proteases generated bioactive peptides with potential health benefits (Barkia et al, 2019).…”
Section: Sources Of Bioactive Peptidesmentioning
confidence: 99%